REVITALISASI KELOMPOK KERJA GURU DALAM MENGEMBANGKAN KURIKULUM SATUAN PENDIDIKAN SEKOLAH DASAR DI KOTA SEMARANG - Fakhruddin, - (Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2011)
KKG as one of Teacher Community expected to improve service quality and educational outcomes. The issues are, how the mechanism of cluster working groups of teachers in improving the quality of learning, whether the potential material and nonmaterial which can be used as a source of development of teachers in the management of learning, and how to support and empowerment of teacher working group in understanding and implementing the curriculum level education units. Data collection was taken by using questionnaire research and documentation. Questionnaires are used to reveal the mechanisms, programs, support and empowerment of KKG. Documentation are used to reveal data about the number of primary schools, learners and Cluster KKG. Results showed that the mechanism of development and management of the KKG is set through consultation according to the annual periodicity, further to enhance competence through sharing knowledge, skills and attitudes, test ideas, and discussion. The results suggest that preparation of KKG program tailored to the needs and problem of teachers in classroom learning, the importance of monitoring and evaluation continues with the instruments and the framework of implementation of SBC by every teacher in class need to attempt- efforts to obtain the support of various parties.